Development of a Popular Scientific Book about Pulai Population Structure (Alstonia scholaris) in the Lake Sari Embun Region, South Kalimantan - Putri Wulan Sari AJ; Dharmono Dharmono; Kaspul Kaspul (Journal Of Biology Education Research (JBER), 2024)
Indonesia has high biodiversity, one of the plants that is widely distributed in Indonesia is Pulai (Alstonia scholaris), The Island is used as a traditional medicinal plant. Pulai trees can be found in the Danau Sari Embun area, Tanah Laut Regency and have the potential to be a source of learning, so the results of the Population Structure study are made in the form of a locally based PSB. This research aims to describe the structure of Pulai (Alstonia scholaris) in the Danau Sari Embun area, Tanah Laut Regency, describe the process of developing BIP. Population structure of Pulai (Alstonia scholaris) in the Danau Sari Embun area, Tanah Laut Regency, Describe the feasibility of the population structure of BIP Pulai (Alstonia scholaris). The method used is the RD (Research and Development) research method and the Plomp model. The results obtained by the number of Islands found in the reproduction phase and in the post-reproduction phase, thus showing a picture of the form of Srukpop, namely pot paintings, the PSB about Island Population Structure that was developed was declared very valid. So it can be concluded that PSB teaching materials can be used as teaching materials in the learning process.